Engagement in the Educational Sector: Is the Equation Different? The Case of Oman’s Educational Sector - AL SENANI, KHALID MOHAMMED OBAID (2016)
Orientation: Discussion of the factors affecting employee engagement is important for practitioners and researchers alike in educational setting in Oman. Research purpose: The aim of the current study is to explore the drivers that influence teaching and non-teaching employees to engage to their work and relate them to updated literature review in the topic of employee engagement. Motivation for the study: the knowledge attained from this study grounds our understanding of employee engagement in area like Oman that has not been visited by research studies yet. It may contribute to the global effort in this subject. Research design, approach and method: A ranking survey of three lists of employee engagement factors that have been collected from variety of research papers and consultancy reports. Sample of 1000+ was addressed in educational field. Lists of top priorities and least priorities were arranged, ranked and discussed. A well-known survey program was used. Main findings: The study found that employees in the educational sector ranked 'organisational justice' as top priority to engage in their work and ranked 'sense of accomplishment' as the least priority. There are also some differences between demographics and organisational positions among employees when ranking priorities of what drives them to engagement. Pratical/managerial implications: Suggestions to enhance the work environment based on the study findings are discussed in two aspects. One, how the targeted organisation improves employee engagement and two what intervention that educational managers and strategists should do to enable teaching and non-teaching employees to engage fully in their work. Contribution/value-add: This study contributes to global efforts of how to make workplace more engaging and adds value to global understanding of a local culture (Oman)